(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Gibberellic acid (GA3) was sprayed with eleven doses viz. 0, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 ppm at the primordia initiation stage to evaluate its effect on the growth and yield performance of Oyster Mushroom. At 10 ppm level GA3 gave the highest economic yield and dry weight. Application of GA3 increased the fresh economic yields to about 30% and 34%, while 80% and 115% dry weights increase occurred compared to the control at first and second harvests, respectively. GA3 showed a positive effect on number of effective fruiting body, stalk length, pileus diameter, biological yield, economic yield and dry economic yield. The result suggested that GA3 at 10 ppm/packet would be the best possible concentration for production of Oyster Mushroom. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18196 J. Bangladesh Agril. Univ. 11(1): 5-10, 2013